COSMIC RAY INTENSITY VARIATIONS DURING 1964. - Sandstrom,A. E.; Dyring,E.; Ekstrom,L.; Lindgren,S.; Sporre,B. (1965)
Cosmic ray intensity variations were recorded by one neutron monitor, two cubical telescopes and six inclined telescopes in Uppsala and Kiruna. Tables and figures give a detailed account of diurnal and semidiurnal variations during 1964. Only one decrease is illustrated in an one-hour diagram. (Author) Available copy will not permit fully legible reproduction. Reproduction will be made if requested by users of DDC. Copy is available for public sale. Continuation of Contracts AF61 514 1312, AF61 052 614.